PENGARUH SISTEM MERIT TERHADAP SEMANGAT KERJA APARATUR SIPIL NEGARA DI KANTOR SEKRETARIAT DAERAH KOTA MANADO - TONDOWANA, ABDIEL THEOPILUS; RORONG, ARIE JUNUS; LONDA, VERY (Sam Ratulangi University, 2018)
One of the elements of government in Indonesia is the state civil apparatus. Its task is to assist thegovernment in serving the needs of the people where the people are the main elements in democracy. Theproblems encountered in the apparatus of the regional secretariat of Manado City in 2017 are still manyacts of abuse of authority and positions owned by the apparatus, one of which is nepotism. Nepotism alsotrigger social jealousy among officials because they feel unfairly treated in the promotion processpositions that are not in accordance with the level of career. Apparatus has the ability and expertise incompleting the task, but does not have good discipline. Late arriving at the office, wandering around atwork, dressed unkempt and other things that violate the regulations of the agency. Delaying work thatcould have been completed that day but not done, stalling work time to make the work pile up. Theapparatus becomes lazy and unproductive. Does not show his professionalism as a civil servant of the statein charge of serving the community. Arise attitudes underestimate the job because they realize he has theability and expertise that is expected and become the mainstay of the leadership. And lack of appreciationfrom the leadership to his subordinates for the ability and the work that has been achieved. Based on theresults of test and data analysis using quantitative methods, it is concluded that the merit system has aneffect and has a positive influence on working spirit. With the merit system will improve the working spiritof state civil apparatus in the Regional Secretariat office of Manado City. It is not enough to have a goodcivil apparatus management system, but also the spirit of work to motivate the apparatus in order toimprove discipline and achieve work performance in line with expectations.Keywords: Merit System, Working Spirit, State Civil Apparatus.